Portfolio holdings in the euro area - home bias and the role of international, domestic and sector-specific factors - Axel Jochem; Ute Volz (Deutsche Bundesbank, 2011)
This paper aims to identify the determinants of portfolio restructuring in EMU member states since the introduction of the euro and especially during the financial turbulence of the past years. We find that, besides exchange rate volatility and traditional indicators of information and transaction costs, the perception of sovereign risk has become more important as a determinant of portfolio allocation. The shares of financial corporations have been affected disproportionately by this development. At the same time, banks substantially reduced their international investment, possibly the result of a deleveraging process.
Keywords: F30; F32; F36; G11; 330; Financial Integration; Home Bias; Institutional Sectors; Financial Crisis